2010
DOI: 10.2166/wh.2010.056
|View full text |Cite
|
Sign up to set email alerts
|

Levels and patterns of fecal indicator bacteria in stormwater runoff from homogenous land use sites and urban watersheds

Abstract: Routine stormwater monitoring programs focus on quantification of average fecal indicator bacteria (FIB) concentration at the terminal watershed discharge point. While important for permit compliance, such monitoring provides little insight into relative bacteria levels from different land use types or the mechanisms that influence FIB concentrations. The goal of this study was to quantify the relative levels and flux patterns of Escherichia coli, enterococci, and total coliforms from representative land use (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…In urban areas without adequate wastewater treatment or stormflow mitigation management, heavy rainfall washes off FIB and other contaminants from the ground surface12. In rural areas, especially in areas with bare soil and/or annual crops, similar heavy rainfall leads to the erosion of soil and, hence of any faecal matter on the soil surface313.…”
mentioning
confidence: 99%
“…In urban areas without adequate wastewater treatment or stormflow mitigation management, heavy rainfall washes off FIB and other contaminants from the ground surface12. In rural areas, especially in areas with bare soil and/or annual crops, similar heavy rainfall leads to the erosion of soil and, hence of any faecal matter on the soil surface313.…”
mentioning
confidence: 99%
“…In evaluating bacteria concentrations in stormwater runoff, Tiefenthaler et al . () found patterns within storms with the highest bacterial concentrations often preceding peak flow, while Edwards et al . () noted peaks in FIB following peak flow.…”
Section: Resultsmentioning
confidence: 95%
“…When stormwater runoff is considered, the relationship of flow with bacteria concentrations becomes more complicated and depends greatly on land cover and land use characteristics and the timing and intensity of stormwater contributions. In evaluating bacteria concentrations in stormwater runoff, Tiefenthaler et al (2011) found patterns within storms with the highest bacterial concentrations often preceding peak flow, while Edwards et al (1997) noted peaks in FIB following peak flow. Depending on the watershed, contributions associated with stormwater runoff may potentially mask contributions from birded bridges, so sources associated with ambient and stormwater flows may need to be considered separately in impaired watersheds.…”
Section: Estimation Of Active Bird Nests and Fecal Countsmentioning
confidence: 99%
“…Research suggests that in some watersheds which are impaired due to high bacteria, indicator bacteria levels increase with increasing flow rate, usually immediately after significant rainfall events (Tiefenthaler et al, 2011;Marsalek and Rochfort, 2004). Ironically, it is under increased flow conditions after rainfall events that Twelve Mile Creek experiences its highest use by paddlers (AWA, 2014).…”
Section: Study Sitementioning
confidence: 99%